Characterization of a mutant samhd1 zebrafish model implicates dysregulation of cholesterol biosynthesis in Aicardi-Goutières syndrome - Withers, Sarah E.; Rowlands, Charlie F.; Tapia, Victor S.; Hedley, Frances; Mosneag, Ioana-Emilia; Crilly, Siobhan; Rice, Gillian I.; Badrock, Andrew P.; Hayes, Andrew; Allan, Stuart M.; Briggs, Tracy A.; Kasher, Paul R. (Frontiers in Immunology, 2023)
Aicardi-Goutières syndrome (AGS1-9) is a genetically determined encephalopathy that falls under the type I interferonopathy disease class, characterized by excessive type I interferon (IFN-I) activity, coupled with upregulation of IFN-stimulated genes (ISGs), which can be explained by the vital role these proteins play in self-non-self-discrimination. To date, few mouse models fully replicate the vast clinical phenotypes observed in AGS patients. Therefore, we investigated the use of zebrafish as an alternative species for generating a clinically relevant model of AGS. Using CRISPR-cas9 technology, we generated a stable mutant zebrafish line recapitulating AGS5, which arises from recessive mutations in SAMHD1. The resulting homozygous mutant zebrafish larvae possess a number of neurological phenotypes, exemplified by variable, but increased expression of several ISGs in the head region, a significant increase in brain cell death, microcephaly and locomotion deficits. A link between IFN-I signaling and cholesterol biosynthesis has been highlighted by others, but not previously implicated in the type I interferonopathies. Through assessment of neurovascular integrity and qPCR analysis we identified a significant dysregulation of cholesterol biosynthesis in the zebrafish model. Furthermore, dysregulation of cholesterol biosynthesis gene expression was also observed through RNA sequencing analysis of AGS patient whole blood. From this novel finding, we hypothesize that cholesterol dysregulation may play a role in AGS disease pathophysiology. Further experimentation will lend critical insight into the molecular pathophysiology of AGS and the potential links involving aberrant type I IFN signaling and cholesterol dysregulation.